Distribution Pattern of Avian Species in Sultanpur National Park, Haryana, India with Special Reference to Residential and Migratory - Kumar, Shiv; Singh, Sonalika; Sharma , Laxmi Kant; Bohra , Dau Lal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
From September 2021 to March 2023, we embarked on a journey to document the avian wealth of Sultanpur National Park in Haryana, India. Our survey revealed a stunning tapestry of 105 bird species, representing 16 orders and 40 families. While 108 species held Least Concern status, two precious residents, the Saras Crane (Grus antigone) and White-necked Stork (Ciconia episcopus), teetered on the edge of vulnerability, facing mounting threats. The Indian Silverbill, Scaly-breasted Munia, Plain Martin, Wire-Tailled Swallow, and Bay-backed Shrike joined their ranks, listed as vulnerable in the IUCN Red Data Book. Our research suggests that Sultanpur National Park holds the potential to become a haven for these at-risk species. With dedicated efforts to ensure year-round water availability and the strategic planting of native trees like Ficus religiosa, Ficus bengalensis, Azadirachta indica, Acasia nilotica, and Mangifera indica, we can create a sanctuary for Painted Storks, White-necked Storks, and Black-necked Storks. Additional platforms could further encourage the proliferation of Saras Cranes and White-necked Storks, giving them the perfect stage to raise their young. This study serves as a call to action, both for the public and the state government to up their game in the area of conservation of wildlife species. By understanding the park's rich avian tapestry and the dangers it faces, we can mobilize support for its conservation. Protecting Sultanpur National Park and its irreplaceable birdlife is not just a responsibility, but a privilege. Let us join hands to ensure the skies above this national treasure remain forever filled with the songs and wings of its feathered residents.